2021
DOI: 10.5603/cj.a2021.0168
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on in-hospital cardiac arrest outcomes: An updated meta-analysis

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Similar to our finding, in a meta-analysis by Bielski et al, subgroup analysis comparing ROSC between COVID-19 and non-COVID-19 patients found lower rate of ROSC in the COVID-19 population (33.9%) as compared to the non-COVID-19 patients (52.1%) [21]. A proportional prevalence meta-analysis including 4 studies and 943 IHCA patients with COVID-19 by Mir et al [22] reported a lower pooled prevalence of ROSC (39%) than our study (52.83%).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our finding, in a meta-analysis by Bielski et al, subgroup analysis comparing ROSC between COVID-19 and non-COVID-19 patients found lower rate of ROSC in the COVID-19 population (33.9%) as compared to the non-COVID-19 patients (52.1%) [21]. A proportional prevalence meta-analysis including 4 studies and 943 IHCA patients with COVID-19 by Mir et al [22] reported a lower pooled prevalence of ROSC (39%) than our study (52.83%).…”
Section: Discussionsupporting
confidence: 92%
“…if necessary. We performed a systematic assessment of bias in the included studies using the Cochrane criteria [ 22 ]. For this purpose, a tool for Risk Of Bias In Non-randomized Studies of Interventions (ROBINS-I) [ 23 ] was used.…”
Section: Methodsmentioning
confidence: 99%
“… 49 In a meta-analysis of 3 studies of in-hospital cardiac arrest, SARS-CoV 2 infection was associated with lower rates of shockable rhythm (9.6% vs. 19.8%, p< 0.001), lower rates of ROSC (33.9% vs. 52.1%, p< 0.001), and higher 30-day mortality (77.2% vs. 59.7%, p=0.003). 50 …”
Section: Introductionmentioning
confidence: 99%